The influential image of nighttime urban public park in forming place identity /Mohd Riduan Ngesan, Hafazah Abdul Karim and Syed Sobri Zubir. - Ngesan, Mohd Riduan; Abdul Karim, Hafazah; Zubir, Syed Sobri (Universiti Teknologi MARA Cawangan Selangor, 2018)
The design of urban public park is an important factor which influence urban community leisure. The objective of this study is to investigate the community perceptions on nighttime leisure activities in urban public park. The questionnaire survey is done in Padang (green field) located in the urban center of Shah Alam and Putrajaya using random stratifies technique. There are four types of variable studied related to nighttime leisure in an urban public park namely comforts, conveniences, safety and nighttime leisure. The findings from this study are expected to show a positive perception of nighttime leisure in urban public park towards urban community.